Prevalence and associated factors of basilar artery dolichosis in patients with acute cerebral infarction - Cao, Shugang; Zhai, Mingfeng; He, Jun; Cui, Ping; Ge, Tingting; Wang, Jian; Xu, Wen’an; Wang, Rongfeng; Xia, Mingwu (Frontiers in Medicine, 2023)
Introduction: Little attention has been given to the factors associated with basilar artery (BA) dolichosis. This study aims to elucidate the prevalence and associated factors of BA dolichosis in patients with acute cerebral infarction (ACI). Methods: We collected the clinical and laboratory data of 719 patients with ACI admitted to our department. Magnetic resonance angiography was used to evaluate the geometric parameters of the BA and intracranial vertebral arteries (VAs). A BA curve length > 29.5 mm or bending length (BL) > 10 mm was identified as BA dolichosis. Univariate and multivariate logistic regression were performed to determine the factors associated with BA dolichosis. Results: Among 719 patients with ACI, 238 (33.1%) demonstrated BA dolichosis, including 226 (31.4%) with simple BA dolichosis and 12 (1.7%) with basilar artery dolichoectasia (BADE). Pearson correlation analyses showed that BA curve length was positively correlated with BL (r = 0.605). Multivariate logistic regression analysis demonstrated that current smoking (OR = 1.50, 95% CI: 1.02-2.21, P = 0.039), diabetes mellitus (OR = 1.66, 95% CI: 1.14-2.41, P = 0.008), BA diameter (OR = 3.04, 95% CI: 2.23-4.13, P < 0.001), BA bending (OR = 4.24, 95% CI: 2.91-6.17, P < 0.001) and BL (OR = 1.45, 95% CI: 1.36-1.55, P < 0.001) were significantly associated with BA dolichosis. Conclusion: This study suggests that BA dolichosis was common in patients with ACI, and the morphological parameters of the vertebrobasilar artery and acquired risk factors (including smoking and diabetes) were risk factors for BA dolichosis.